A COGNITIVE‑LINGUISTIC ANALYSIS OF SEMANTIC FORMATION IN LEXICALIZED MULTIWORD EXPRESSIONS - Dr. Ammar Adam Abdelnabi Mohamed (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Linguists agree that a linguocultureme is a fundamental linguistic entity that blends linguistic structure and cultural context cohesively. When discussing vocabulary that is distinctive to a culture, it is important to emphasise the interplay between stylistically distinct words and their cultural connotations. This article explores the cognitive aspect of meaning formation by analysing English phraseological units. These units, comprising idioms, collocations and other fixed expressions, are linguistic manifestations of cognitive processes that encapsulate cultural, social and cognitive norms. This research examines a diverse corpus of English phraseological units to investigate how cognitive mechanisms influence the formation and interpretation of meaning within these lexical units. Drawing upon cognitive linguistics and psycholinguistic theories, the study explores the role of conceptual metaphors, image schemas and cognitive frames in shaping the semantics and pragmatics of phraseological expressions. Additionally, the article examines the impact of cultural and contextual factors on the cognitive processing of phraseological units, highlighting the interplay between language, cognition, and culture. Through a combination of qualitative and quantitative analyses, the research elucidates the cognitive mechanisms underlying the construction of meaning in English phraseological units, thereby contributing to our understanding of how language reflects and shapes cognitive processes. The findings have implications for language teaching, cross-cultural communication and computational linguistics, providing insights into the cognitive basis of meaning formation in natural language use.